INCOME AND RISK DETERMINATION OF SHALLOT FARMING BUSINESS IN WANASARI DISTRICT, BREBES REGENCY, INDONESIA - Roessali, Wiludjeng; Mukson, Mukson; Prastiwi, Wahyu Dyah (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2024)
In every agricultural business, farmers face the phenomenon of farming risk. Climate-related production risk, market risk, financial risk, and institutional risk are some of the dangers faced. This study aims to analyze the level of risk and risk mapping faced by farmers and its impact on shallot farming income. This study was conducted in the shallot center area in Wanasari District, Brebes Regency, Central Java, Indonesia from April to May 2023. The survey was conducted using semi-structured interviews and questionnaires on the level of shallot farming risk and factors that influence farmers' income. The analysis was carried out using risk mapping and multiple regression techniques. The results of the study showed that the production risk, market risk, and financial risk of shallot farmers in the study area were included in the high category, while institutional risk was included in the moderate group. The shallots produced per hectare reached 12.76 tons. The factors that influence shallot farming income are land area, productivity, total costs and shallot farmers' risk awareness. Meanwhile, the price of shallots and the level of risk did not significantly affect shallot farming income.